Consensus document on palliative care in cardiorenal patients - Bonanad, Clara; Buades, Juan M.; Leiva, Juan Pablo; De la Espriella, Rafael; Marcos, Marta Cobo; Núñez, Julio; García-Llana, Helena; Facila, Lorenzo; Sánchez, Rosa; Rodríguez-Osorio, Laura; Alonso-Babarro, Alberto; Quiroga, Borja; et al. (Frontiers in Cardiovascular Medicine, 2023)
There is an unmet need to create consensus documents on the management of cardiorenal patients since, due to the aging of the population and the rise of both pathologies, these patients are becoming more prevalent in daily clinical practice. Chronic kidney disease coexists in up to 40%–50% of patients with chronic heart failure cases. There have yet to be consensus documents on how to approach palliative care in cardiorenal patients. There are guidelines for patients with heart failure and chronic kidney disease separately, but they do not specifically address patients with concomitant heart failure and kidney disease. For this reason, our document includes experts from different specialties, who will not only address the justification of palliative care in cardiorenal patients but also how to identify this patient profile, the shared planning of their care, as well as knowledge of their trajectory and the palliative patient management both in the drugs that will help us control symptoms and in advanced measures. Dialysis and its different types will also be addressed, as palliative measures and when the decision to continue or not perform them could be considered. Finally, the psychosocial approach and adapted pharmacotherapy will be discussed.